Certification of a pharmacopoeial reference standard for potency testing of recombinant interferon α-2b - L. A. Gaiderova; Yu. N. Lebedeva; T. N. Lobanova; E. K. Lipatova; R. A. Volkova; O. V. Fadeikina (Биопрепараты: Профилактика, диагностика, лечение)
SCIENTIFIC RELEVANCE. Potency testing of recombinant interferons requires a reference standard. The availability of International Standards (ISs) that are commonly used to assess the quality of recombinant interferons is currently limited. Therefore, the quality of interferons should be assessed using pharmacopoeial reference standards (RSs) certified using ISs (if available).AIM. This study aimed to certify a pharmacopoeial RS for potency testing of recombinant interferon α-2b.MATERIALS AND METHODS. The potency determination involved comparing the inhibition of the virus-induced cytopathic effect observed in cell culture with the candidate RS and the WHO International Standard for Human rDNA-derived interferon α-2b. The study used A-549 and MDBK cell lines with encephalomyocarditis (EMC) and vesicular stomatitis (VSV) viruses. The authors followed the requirements of the State Pharmacopoeia of the Russian Federation (Cell-Culture Bioassays for Interferon Products, OFS.1.7.2.0002.15). The results were recorded using instrumental and visual methods. The calculations used mathematical statistics. To factor in the influence of intermediate precision, the authors applied Student’s t-test.RESULTS. The authors developed a certification programme and procedure and certified the pharmacopoeial RS for recombinant human interferon α-2b (rhIFN α-2b) to identify the corresponding medicinal products (by virus neutralisation) and test their potency (by antiviral activity in cell culture). Upon receipt, the candidate RS was verified for compliance with regulatory specifications. According to the test results, the potency of the candidate pharmacopoeial RS was 4.47×10⁸ IU/mL, and the expanded uncertainty was 8.12×10⁷ IU/mL, with a coverage factor of k=2 and a confidence level of 95%. The pharmacopoeial RS for rhIFN α-2b was considered to have the same shelf-life period as the corresponding medicinal products  if stored at a temperature not higher than –40 ºC. When thawed, the pharmacopoeial RS for rhIFN α-2b can be stored at a temperature of 2–8 ºC for up to 1 month.CONCLUSIONS. Upon certification for potency testing, the pharmacopoeial RS for rhIFN α-2b has been included in the Register of Reference Standards of the Russian Pharmacopoeia as Recombinant Human Interferon α-2b (Potency) FSO.3.2.00455. The introduction of this pharmacopoeial RS will help to conduct the identification and potency testing of all Russian interferon α-2b products at an appropriate scientific and methodological level. As a result, Russian pharmaceutical manufacturers and quality control agencies will no longer depend on imported ISs.